Proceedings of the 29th Annual International ACM SIGIR Conference on Research and Development in Information Retrieval 2006
DOI: 10.1145/1148170.1148188
|View full text |Cite
|
Sign up to set email alerts
|

Respect my authority!

Abstract: We present an approach to improving the precision of an initial document ranking wherein we utilize cluster information within a graph-based framework. The main idea is to perform re-ranking based on centrality within bipartite graphs of documents (on one side) and clusters (on the other side), on the premise that these are mutually reinforcing entities. Links between entities are created via consideration of language models induced from them.We find that our cluster-document graphs give rise to much better re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(1 citation statement)
references
References 37 publications
0
0
0
Order By: Relevance
“…Proposing new ranking query-specific cluster strategies has been a hot research topic for many years (Leuski, 2001), and suggested solutions base on a cluster-against-query representation comparison (Liu & Croft, 2004) (Liu & Croft, 2008). Some document retrieval frameworks make use of extra features, including inter-cluster and clusterdocument similarities (Kurland & Lee, 2006) (Kurland & Domshlak, 2008) (Kurland & Krikon, 2011). Query expansion (QE) is another way to heighten document retrieval systems accuracy (Hiteshwar & Akshay, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Proposing new ranking query-specific cluster strategies has been a hot research topic for many years (Leuski, 2001), and suggested solutions base on a cluster-against-query representation comparison (Liu & Croft, 2004) (Liu & Croft, 2008). Some document retrieval frameworks make use of extra features, including inter-cluster and clusterdocument similarities (Kurland & Lee, 2006) (Kurland & Domshlak, 2008) (Kurland & Krikon, 2011). Query expansion (QE) is another way to heighten document retrieval systems accuracy (Hiteshwar & Akshay, 2019).…”
Section: Introductionmentioning
confidence: 99%